Paper domes and shelters - Jerzy F. Latka (A+BE: Architecture and the Built Environment)
This part of the dissertation is dedicated to the practical approach to cardboard as a building material through prototyping. Taking a practical approach here means conducting research by design and prototyping architectural structures in which paper and its derivatives are used as the main structural material. The theoretical research and knowledge presented in the previous chapters of the dissertation will be now used as input.